Dendronized fullerene-porphyrin conjugates in ortho, meta, and para positions: A charge-transfer assay - Krokos, Evangelos; Schubert, Christina; Spaenig, Fabian; Ruppert, Michaela; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry-An Asian Journal, 2012)
The physicochemical characterization, that is, ground and excited state, of a new series of dendronized porphyrin/fullerene electron donor-acceptor conjugates in nonaqueous and aqueous environments is reported. In contrast to previous work, we detail the charge-separation and charge-recombination dynamics in zinc and copper metalloporphyrins as a function of first- and second-generation dendrons as well as a function of ortho, meta, and para substitution. Both have an appreciable impact on the microenvironments of the redox-active constituents, namely the porphyrins and the fullerenes. As a matter of fact, the resulting charge-transfer dynamics were considerably impacted by the interplay between the associated forces that reach from dendron-induced shielding to dipole-charge interactions. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.